(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: 1/ Introduction. 2/ Keyword subject access. 3/ Subject indexing. 4/ User system interaction. 5/ Subject heading systems. 6/ Language in information retrieval. 7/ Database. 8/ Dewey decimal and library of congres classifications. 9/ Evaluation of subject retrieval.
Keywords: Online library catalogs,Subject cataloging,Machine-readable bibliographic data; Subject access.,Data processing